Curriculum Management Development Strategy in Madrasah (Visionary Studies in Educating Students at the Elementary Education Level) - Neliwati Neliwati; Deni Khurniawan; Yulita Suyatmika; Siti Rahma Ismiatun (Jurnal Basicedu, 2022)
The curriculum contains indicators of the success of the learning process, starting from aspects of planning, implementation (core activities) and closing. For this reason, the curriculum requires effective management and development strategies, so that it is adaptive to the times and in accordance with the needs of students. This study aims to analyze curriculum management and development strategies at MTsN 4 Mandailing Natal. This study uses a qualitative approach with descriptive analytical study method. Data collection was carried out systematically through interview, observation and documentation studies. Furthermore, the data were analyzed using reduction techniques (data sorting), data presentation, and drawing conclusions. The results of this study conclude that the development of curriculum management in madrasas is optimized by the Head of MTsN 4 Mandailing Natal through 4 madrasa internal strategies, namely (1) curriculum development based on teaching materials must be equipped with references (books) as teaching companions; (2) teachers are required to be proactive in facilitating student learning processes and connecting students with various learning resources; (3) providing adequate teaching aids; and (4) providing direct guidance from the head of the madrasa to teachers in training activities or quality improvement workshops.